Response of direct dry seeded rice (Oryza sativa L.) to seeding dates and seed rates - Rangit, JD; Sharma, S; Gautam, DD (Agronomy Journal of Nepal, 2013)
Field studies to access seed rate, seeding dates, and weed infestation in direct dry sseded rice (Khumal -4) were carried out under rice-wheat rotation system at Khumaltar during 2005/06 -2007/08. The broadleaf weeds: Ageratum conyzoides, Commelina diffusa, Eclipta prostrata, Amaranthus veridis, Coronopus didymus, Lactuca sp. the grassy weeds: Echinochloa colona, Cynodon dactylon, and Paspalum distichum and the sedges: Cyperus difformis and C iria were recorded. E colona was the dominant weed in the second year, however A conyzoides was pronounced in the first year. A conyzoides showed an increasing trend over years and became a dominant species ranging from 2-13/0.25m2 in the 1st year and 53 -144/0.25m2 in the 3rd year. Significant interaction effect on total weed number/0.25 m2 was recorded in the 2nd seeding date in all seed rates. Significantly higher weed numbers were recorded in 2nd seeding date and 20 kg/ha seed rate in the 3rd year. There was no significant interaction between different seed rate and seeding date on the gall formation due to Meloidogyne graminicola. Plant height, tillers/m2, number of seeds/panicle, and grain yield were not significantly affected due to seeding dates except plant height in 2005/06. Number of tillers/m2 was significantly different among seed rates and showed slightly increasing trend with higher seed rates. But there was no significant different in grain yield among seed rates except in the year 2005/06. Dry straw weight did not show consistent results among seeding dates. The present study showed that rice seeding can be done in mid May with the seed rates 30–50 kg/ha. DOI: http://dx.doi.org/10.3126/ajn.v1i0.7538 Agronomy Journal of Nepal (Agron JN) Vol. 1: 2010 pp.16-22